GK-2 new drug with neuroprotective properties the study of acute and chronic toxicity of the finished dosage forms - A. V. Sorokina; S. V. Alekseeva; I. A. Miroshkina; A. V. Volkova; V. V. Zabrodina; K. S. Kachalov; I. V. Alekseev; A. D. Zaharov; P. Yu. Povarnina; A. D. Durnev (Фармакокинетика и Фармакодинамика)
Resume. The paper presents the data of preclinical studies of the acute and chronic toxicity of the finished dosage form of the compound GK-2, which has neuroprotective properties. It has been established that GK-2 does not cause the death of animals after a single intravenous administration in the maximum allowable volumes to outbred white mice and rats of both sexes. The average lethal doses of HA-2 were determined for intraperitoneal administration. In experiments on mice in females, the LD50 was 15.4 (14.5-16.4) g / kg. In males, the LD50 is 15.7 (14.6-16.9) g / kg. In experiments on rats in females and males, the LD50 was 6.9 (4.5-10.6) g / kg. Daily intravenous administration of the finished dosage form to purebred white rats and rabbits of the chinchilla breed of both sexes for one month at a dose corresponding to therapeutic - 1 mg / kg (in terms of active substance) and exceeding it ten times - 10 mg / kg (in terms of active substance) allowed to establish that GK-2 does not affect the integral indicators. The exceptions were reduced body weight gain and a dose-dependent decrease in feed and water intake in female rats of the experimental groups. In clinical, laboratory, pathological and histological studies performed in accordance with the general protocol, the toxic effects of GK-2 have not been established.